Revisiting The Contemplative Life in The Contemporary Era - Simarmata, Petrus; Pinem, Milda Longgeita; Pinem, Firdaus Lisinius (Undiksha, 2024)
This article explores the relevance and potential benefits of contemplative life in the contemporary world. It discusses the background of the contemplative tradition and its historical context, as well as its current role in modern society. The article also describes the methods used to conduct a literature review of relevant research and texts, as well as an analysis of contemporary applications of contemplation in various fields and contexts. Databases searched included JSTOR, Google Scholar, and PubMed. The results and discussion section of the article covers the key findings from the literature review and analysis, highlighting both the potential benefits and challenges associated with the practice of contemplative techniques in the modern world. The conclusion of this article suggests that while the contemplative life may face challenges in contemporary society, it remains a relevant and beneficial practice for individuals seeking personal growth, spiritual development, and enhanced well-being.